15th Annual GaAs IC Symposium
DOI: 10.1109/gaas.1993.394470
|View full text |Cite
|
Sign up to set email alerts
|

0.6 V suppy voltage 0.25 μm E/D-HJFET(IS/sup 3/T) LSI technology for low power consumption and high speed LSIs

Abstract: A new technology of fabricating 0.25 pm gate E Dheterojunction FET LSIs is developed as a step towards the development of ultra low supply voltage LSIs. This technology, which is based upon all dry-process techniques, includes the formation of a 0.25 pm gate opening through the use of optical lithography and inner Si02 sidewalls. The fmax and the gmmax for a Y-shaped gate E-HJFET are 108 GHz and 520 mS/mm, respectively. Excellent performances are obtained with DCFL ring oscillators using n-AlGaAs/i-InGaAs pseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…The MUX and DEMUX were fabricated by using 0.35-m gate -AlGaAs/ -InGaAs IS 3 HJFET's [1], which had of 45 GHz and of 120 GHz. The delay time measured by a DCFL 51-stage ring oscillator was 26 ps/gate with a power consumption of 0.2 mW/gate at a supply voltage of 0.7 V.…”
Section: Circuit Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The MUX and DEMUX were fabricated by using 0.35-m gate -AlGaAs/ -InGaAs IS 3 HJFET's [1], which had of 45 GHz and of 120 GHz. The delay time measured by a DCFL 51-stage ring oscillator was 26 ps/gate with a power consumption of 0.2 mW/gate at a supply voltage of 0.7 V.…”
Section: Circuit Performancementioning
confidence: 99%
“…One effective way to decrease power consumption is to reduce the supply voltage. Direct-coupled field-effect transistor (FET) logic (DCFL) circuits based on i-InGaAs channel pseudomorphic heterojunction FET's (HJFET) on GaAs substrates [1], [2] are suitable for this, because these FET's have high cutoff frequency and low drain current saturation voltage. We have already demonstrated that DCFL D-FF's based on these FET's operated at 10 Gb/s with supply voltage below 1 V [3]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…Minimizing source parasitic resistance (Rs) is also effective in lowering Vhee. Our 0.25pm gate HJFET fabricated by "inner sidewall assisted super self-aligned technology (IS3) [2]" decreased Rs by minimizing gate-to-source …”
Section: Id Ic Design and Fabricationmentioning
confidence: 99%
“…The prescaler IC was fabricated by using a 0.2-pm-gate n-AlGaAs/i-InGaAs IS3HJFET [12]. The obtained g, , , , was 420 mS/mm, f , , , was 160 GHz, and fT was 70 GHz at V,, of 0.5 V. To avoid input signal waveform distortion, 50-9 on-chip termination was used.…”
Section: Circuit Performancementioning
confidence: 99%
“…To decrease power consumption, the supply voltage must be reduced. Since compound semiconductors have inherently high electron mobility, GaAs HJFET circuits can provide high-speed performance and low power consumption at low supply voltages of less than 1 V [12].…”
Section: Introductionmentioning
confidence: 99%